The Mediating Role of Brand Performance on the Relationship between Confusion - Brand Loyalty and Uncertainty Avoidance – Brand Loyalty - Çiğdem Unurlu (İzmir İktisat Dergisi, 2019)
The purpose of this study is to determine whether brand performance has mediating effect on the relationship between confusion - brand loyalty and between uncertainty avoidance – brand loyalty or not. The proposed model was tested on 437 participants. As a result of the analysis, it was revealed that brand performance has a full mediating effect on the relationship between the confusion and brand loyalty, and a partial mediating effect on the relationship between the uncertainty avoidance and brand loyalty. Also, as a result of the model testing, it was found that uncertainty avoidance explained 28% of the variability in brand performance, confusion explained 14% of the variability in brand performance and also brand performance explained 81% of the variability in brand loyalty. On the other hand, confusion does not directly affect brand loyalty but it affects brand loyalty through brand performance.